A Review About Family Context and Reconstruction Problems in the Austronesian Languages Family - Minsung Cho (Masyarakat Linguistik Indonesia Universitas Andalas, 2020)
Austronesian languages are one of the largest language groups in terms of the number of speakers and also its spread area around the world. The Austronesian languages are assumed to be branched, developed and spread extensively as a result of migration from Taiwan to the south, including the Nusantara archipelago. This literature-based paper attempted to examine the spread and development of the Austronesian languages family as well as the problems in reconstructing the Austronesian languages in the Nusantara archipelago. This writing examined the process and form of words’ reconstruction problems, in Austronesian languages and its relation with its parent form that eventually created the languages that existed in the Malay Archipelago. The results of the reconstruction demonstrated that the inheritance of the language from one generation to the next had created a significant relationship of the current language employed in the Nusantara archipelago with its parent language as well as proved kinship based on elements of similarity as well as innovation or change from its parent, the ancient Austronesian language (proto). The research also discovered that the family relationship of the languages is manifested through the similarity of pronunciation sound form, vocabulary and grammar structure when reconstructed based on the sound similarity found in the languages compared.